Role of language proficiency and personality traits upon the academic performance of undergraduate medical students - Kamlesh Jha; Yogesh Kumar; Tribhuwan Kumar; Ramji Singh; Pramita Dubey (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Academic performance of medical students is governed by various factors. Personality traits such as core self-evaluation (CSE) and locus of control (LOC) are a few of the most important factors that could govern academic performance. The medium of communication is another important factor, especially in a country with language diversity that could affect the academic performance of the new medical entrants. The study aims to examine the effect of LOC, CSE score, and English Language proficiency on the academic performance of undergraduate medical students. MATERIALS AND METHODS: Ninety undergraduate medical students of a premier central government medical institute of India has been recruited for the study after due ethical clearance from the Institutional Ethical Committee. A standard questionnaire for all the parameters to be studied had been filled by the participants. The academic performance has been judged on the basis of the professional examination's marks score. RESULTS: The multiple regression analysis considering all the variables, the English language proficiency appears to be the most important factor with R 2 = 0.106 and P= 0.003. Most of the academic performers have shown the dominance of internal LOC and moderately high CSE scores though not statistically significant. CONCLUSIONS: Language proficiency appears to be one of the most important determinants of academic performance in the medical entrants of Indian subcontinent. LOC and CSE could be an important yardstick for academic performance, but that needs to be confirmed with another study with a bigger data set.